2021
DOI: 10.24093/awej/covid.25
|View full text |Cite
|
Sign up to set email alerts
|

Technology, Pedagogy & Assessment: Challenges of COVID19-Imposed E-Teaching of ESP to Saudi Female PY Students

Abstract: The Coronavirus Disease (Covid-19) triggered substantial shifts in the education systems worldwide as teaching and learning have had to shift from face-to-face to an entirely virtual model due to the closure of educational institutes. The present paper is a descriptive-analytical investigation of the challenges of the current pandemic-imposed E-teaching of English for Specific Purposes (ESP) courses to female preparatory (PY) year students at King Khalid University (KKU). It identifies teachers’ and students’ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…According to most of the teacher participants, online assessment seems to be an inefficient process to evaluate the students' performance and learning. In accordance with Alvi, Bilal, & Alvi (2021) in their study confirmed that Arab World English Journal www.awej.org ISSN: 2229-9327 50 There is a sweeping agreement among almost 95% percent of the participants that teaching and learning English in Medicine in the traditional face-to-face method is far better and more effective than online learning. Another similar percentage believed that they face technical problems while longing into the university learning management systems due to various reasons of internet connection, system collapses or device technical issues.…”
Section: Discussionsupporting
confidence: 66%
“…According to most of the teacher participants, online assessment seems to be an inefficient process to evaluate the students' performance and learning. In accordance with Alvi, Bilal, & Alvi (2021) in their study confirmed that Arab World English Journal www.awej.org ISSN: 2229-9327 50 There is a sweeping agreement among almost 95% percent of the participants that teaching and learning English in Medicine in the traditional face-to-face method is far better and more effective than online learning. Another similar percentage believed that they face technical problems while longing into the university learning management systems due to various reasons of internet connection, system collapses or device technical issues.…”
Section: Discussionsupporting
confidence: 66%
“…The main plausible reason for this anxiety is that internet connection instability, even for a few minutes, makes teachers concerned that students may miss out on important class content. Alvi et al (2021) relate such recurrent connection problems to technophobia as another emotional challenge experienced by teachers and students alike.…”
Section: Challenges Faced During Online Teachingmentioning
confidence: 99%
“…Similarly, Alvi, Bilal, and Alvi (2021) examined the challenges that the Covid-19 pandemic imposed on university teachers and students of an English for Specific Purposes (ESP) course in Saudi Arabia. Twenty EFL teachers were interviewed while 80 female students in a medical preparatory year responded to a questionnaire.…”
Section: Challengesmentioning
confidence: 99%
“…Alkhannani (2021) looks at the possibilities created by online teaching and learning and the challenges that teachers and learners faced in EFL settings. Alvi, Bilal, & Alvi (2021) adopt quantitative and qualitative methods to examine teachers and students' views regarding the challenges that surround teaching and learning English. Sheera et al, (2022) use semi-structured interviews to explore teachers and students' perceptions of online learning during the pandemic with a special focus on writing.…”
Section: Literature Reviewmentioning
confidence: 99%